Entry regulations, welfare and determinants of market structure - Florin Maican; Matilda Orth (Research Institute of Industrial Economics (IFN), 2015)
We use a dynamic oligopoly model of entry and exit with store-type differentiation to evaluate how entry regulations affect profitability, market structure and welfare. Based on unique data for all retail food stores in Sweden, we estimate demand, recover variable profits, and estimate entry costs and fixed costs by store type. Counterfactual policy experiments show that welfare increases when competition is enhanced by lower entry costs. Protecting small stores by imposing licensing fees on large stores is not welfare enhancing. This study sheds light on the long-run implications of entry regulations for the welfare of differentiated product industries with endogenous entry and exit.
Keywords: L11; L13; L81; 330; Imperfect competition; product differentiation; retail markets; entry; exit; sunk costs; welfare